2004
DOI: 10.1136/bjo.2003.025924
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes in children in Malawi following retinopathy of severe malaria

Abstract: Aim: To investigate whether retinal changes in children with severe malaria affect visual acuity 1 month after systemic recovery. Methods: All children with severe malaria admitted to a research ward in Malawi during one malaria season were examined by direct and indirect ophthalmoscopy. Visual acuity was tested in those attending follow up by Cardiff cards, Sheridan-Gardiner single letters, or Snellen chart. Results: 96 (68%) children attended follow up, of whom 83 (86%) had visual acuity measured. Cardiff ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…3 A mechanism of metabolic steal by intravascular sequestered parasites has been suggested. 11,18 In conclusion these data show that the presence of increasingly severe retinal whitening (retinal CNP/ hypoxia) in CM retinopathy is associated with significant changes in cone b wave function.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…3 A mechanism of metabolic steal by intravascular sequestered parasites has been suggested. 11,18 In conclusion these data show that the presence of increasingly severe retinal whitening (retinal CNP/ hypoxia) in CM retinopathy is associated with significant changes in cone b wave function.…”
Section: Discussionmentioning
confidence: 61%
“…8 It has also been described elsewhere that observed MW seems to be reversible with no adverse visual sequelae. 11 Current data obtained earlier from healthy children, show increasing ERG amplitudes with increasing age. 6 This was therefore identified as an anticipated source of bias before our study.…”
Section: Discussionmentioning
confidence: 88%
“…Thus Plasmodium falciparum was the most common cause of cerebral malaria. Jain, et al had also reported 96%cases of cerebral malaria caused by Plasmodium falciparumin their study [12] . In our study we also found cases of cerebral malaria which were caused by plasmodium vivax which was in accordance with the observation of Ahmed [13] and Gopinathan [14] .…”
Section: Discussionmentioning
confidence: 81%
“…Beare, et al (2004) [9] reported 61% while Birbeck, et al (2010) [10] reported 79% incidence of retinopathy in their studies of cerebral malaria. Mortality reported by various authors in patient having any fundal abnormality was 21% in children (Beare, et al 2004) [9] and 24% in adults (Kochar & Shubhakaran, et al 1998) [11] . In CM groupon the basis of GCS we found that 79% patients with Glasgow score less than or equal to 6 had retinopathy, while only 35% who had Glasgow score more than 6 had retinopathy.…”
Section: Discussionmentioning
confidence: 98%